The MHC and MHC molecules 1 - Kaufman, Jim (Henry Stewart Talks, 2022)
The definition and the central role of MHC molecules, Classical class I and class II MHC molecules, Non-classical MHC molecules, MHC genes and organization in humans and mice, Differences between class I and class II molecules, The function of different MHC molecules in human and mice